2014
DOI: 10.1016/j.worlddev.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Empowerment and Prevalence of Stunted and Underweight Children in Rural India

Abstract: This study investigates whether mother's empowerment measured by her education attainment relative to father's, domestic violence and autonomy is related to children's nutritional status using the three rounds of NFHS data in India. First, mother's relative education is associated with better nutritional status of children in the short run. Second, the quantile regression results show strong associations between women's empowerment and better nutritional status of children in the long run at the low end of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 46 publications
8
110
0
5
Order By: Relevance
“…The influence of the relative bargaining power of women in the household as measured by mother's schooling relative to father's on child nutrition outcomes has been examined by Imai, Annim, Gaiha, and Kulkarni (2014), who find a statistically significant positive influence. Other foci in this literature have included the impact of specific programs such as the Integrated Child Development Services (ICDS) on HAZ (Jain, 2015;Kandpal, 2011).…”
Section: Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the relative bargaining power of women in the household as measured by mother's schooling relative to father's on child nutrition outcomes has been examined by Imai, Annim, Gaiha, and Kulkarni (2014), who find a statistically significant positive influence. Other foci in this literature have included the impact of specific programs such as the Integrated Child Development Services (ICDS) on HAZ (Jain, 2015;Kandpal, 2011).…”
Section: Previous Literaturementioning
confidence: 99%
“…Much of the literature has focused on modeling mean anthropometric outcomes. However, a small set of studies (Borooah, 2005;Imai et al, 2014;Kandpal & McNamara, 2009) has modeled the entire distribution of an outcome such as HAZ by using quantile regression methods. They all have found evidence of heterogeneous effects of key covariates on different parts of the outcome distribution, highlighting the value of allowing for such flexibility.…”
Section: Previous Literaturementioning
confidence: 99%
“…Although inadequate dietary intake and morbidity are immediate causes of undernutrition, studies have shown that household gender inequality relates to high rates of child undernutrition [4, 5]. Women’s empowerment, in terms of control over resources, decision-making and more equitable workloads are all pathways by which nutrition can be improved through agricultural interventions [6, 7]. What are the processes and approaches that can improve gender equity in agrarian, resource-poor settings?…”
Section: Introductionmentioning
confidence: 99%
“…7 While we assume that only parental education affects the bargaining power in the model due to the data constraints, other factors, such as, the difference in ages or labour participation of parents could affect the relative bargaining power (e.g. Imai et al 2012). It is possible that the preferences A i may reflect some factors influencing the bargaining, but we have not modelled the interactions explicitly.…”
Section: Concluding Observationsmentioning
confidence: 99%